Gestational diabetes and risk of breast cancer before age 55 years. (30th August 2021) - Bertrand, Kimberly A; O'Brien, Katie M; Wright, Lauren B; Palmer, Julie R; Blot, William J; Eliassen, A Heather; Rosenberg, Lynn; Sandin, Sven; Tobias, Deirdre; Weiderpass, Elisabete; Zheng, Wei; Swerdlow, Anthony J; et al.
Abstract: Background: The history of gestational diabetes mellitus (GDM) has been associated with breast cancer risk in some studies, particularly in young women, but results of cohort studies are conflicting. Methods: We pooled data from 257 290 young (age <55 years) women from five cohorts. We used multivariable Cox proportional-hazards regression to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association between GDM history and risk of breast cancer, overall and by oestrogen receptor (ER) status, before age 55 years, adjusted for established breast cancer risk factors. Results: Five percent of women reported a history of GDM and 6842 women reported an incident breast-cancer diagnosis (median follow-up = 16 years; maximum = 24 years). Compared with parous women without GDM, women with a history of GDM were not at increased risk of young-onset breast cancer overall (HR = 0.90; 95% CI: 0.78, 1.03) or by ER status (HR = 0.96; 95% CI: 0.79, 1.16 for ER-positive; HR = 1.07; 95% CI: 0.78, 1.47 for ER-negative). Compared with nulliparous women, parous women with a history of GDM had a lower risk of breast cancer overall (HR = 0.79; 95% CI: 0.68, 0.91) and of ER-positive (HR = 0.82; 95% CI: 0.66, 1.02) but not ER-negative (HR = 1.09; 95% CI: 0.76, 1.54) invasive breast cancer. These results were consistent with the HRs comparing parous women without GDM to nulliparous women. Conclusions: Results of this analysis do not support the hypothesis that GDM is a risk factor for breast cancer in young women. Our findings suggest that the well-established protective effect of parity on risk of ER-positive breast cancer persists even for pregnancies complicated by GDM.